A Powtoon Animation Video Development Utilizing a Scientific Approach for Teaching Electrolyte and Non-electrolyte Solutions - Eljinsa, Sehati Mutiara; Zamhari, Muhammad (Postgraduate, University of Mataram, 2024)
Students often experience difficulty learning chemistry because the concepts are abstract and complex and require deep understanding. Therefore, innovation in learning is needed. Educational media is crucial for fostering this innovation. This research aims to develop educational materials on Powtoon animation that utilize a scientific approach to instruct on electrolyte and non-electrolyte solutions and evaluate their efficacy. The method applied was ADDIE model covering five steps, i.e. Analysis, Design, Development, Implementation, and Evaluation. The study involved three peer reviewers, experts in media and materials, five high school chemistry teachers, and thirteen students. Data were collected through questionnaires that were analyzed qualitatively and quantitatively with validated instruments. The result is an interactive learning video in HD mp4 format covering electrolyte and non-electrolyte solutions. The product obtained a score of 82.5% and 95% by material and media experts, respectively, and was categorized as valid. Assessments by teachers and students show scores of 82,5% and 94.4% in a very good category. This Powtoon animation video serves as an alternative and potential medium for teaching chemistry on this topic in the classroom.